Occult and semi-occult constipation in children with monosymptomatic or non monosymptomatic enuresis - Maffei, Helga Verena L. [UNESP]; Vidolin, Eliana; dos Reis, Joceara Neves; de Freitas, Marcia; Cabral, Beatriz Helena; Trigo-Rocha, Flavio (FapUNIFESP (SciELO), 2023)
Background – Functional constipation and enuresis frequently coexist. Constipation treatment often results in resolution or improvement of the enuresis. However, besides the classical presentation, patients can present with occult constipation (OC) diagnosed in complementary evaluation; in addition, semi-occult constipation (SOC) can be detected by means of a detailed questionnaire. Objective – To quantify OC and SOC frequency in children with monosymptomatic or non monosymptomatic enuresis (MNE or NMNE). Methods – Otherwise healthy children/adolescents, with enuresis refractory to behavioral therapy and denying constipation after simple questions, answered a structured bowel habit questionnaire and were submitted to a plain abdominal radiological exam. Constipation was classified considering the Boston diagnostic criteria (to allow diagnosis at initial stages), and fecal loading in the X-ray quantified ≥10 by the Barr score. Children with constipation received a standardized treatment (except 26 “pilot” chil-dren). Results – Out of 81 children, 80 aged 9.34±2.07 years, 52.5% male, were diagnosed with constipation: 30 OC, 50 SOC; 63.75% had MNE, 36.25% NMNE (six NMNE without behavioral therapy). Demographic data and the Barr score were similar for OC and SOC, but SOC children experienced significantly more constipation complications (retentive fecal incontinence and/ or recurrent abdominal pain). Not showing the Bristol Stool Scale (BSS) to 24 “pilot” children, or absence of constipation symptoms accompanying BSS predominantly type 3, in 13 children, did not significantly impact the detection of constipation by the Barr score. Children identifying BSS 3 or ≤2 had similar results. Twenty-eight children, with adequate follow-up after treatment, improved or recovered from constipation at 44 of their 52 follow-up visits. Conclusion – In patients with MNE or NMNE refractory to behavioral therapy, and who initially denied constipation after simple questions, a detailed questionnaire based on the Boston diagnostic criteria detected SOC in 61.7%, and the radiological Barr score revealed fecal loading (OC) in 37.0% of them.
Constipação oculta e semi-oculta em crianças com enurese monossintomática ou não monossintomática.
Keywords: adolescents; Barr score; Children; constipation; enuresis; occult constipation